Implementasi Nilai-niilai Tasawuf sebagai Upaya Pencegahan Narkoba dalam Masyarakat Aceh - Muhammad, Rasyidin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2022)
This research aims to implement Sufism values as an effort to prevent drug abuse within the community, particularly in the city of Lhokseumawe, by involving teachers from Islamic boarding schools. The methods used include identifying Islamic boarding schools, developing outreach materials, conducting interactive outreach sessions, and evaluating through interviews and observations. The results indicate that the outreach materials focusing on the understanding of Sufism, its core values, and their application in preventing drug abuse were well received by the religious teachers (Teungku Bale). Recommendations from this research include the need for continued outreach activities, enhancing teachers' skills, and deepening the outreach materials by involving religious figures and local communities. It is hoped that this research can serve as a model in combating drug abuse through a holistic approach based on spiritual values.